2016
DOI: 10.1097/meg.0000000000000621
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of symptomatic Budd–Chiari syndrome – in favour of early transjugular intrahepatic portosystemic shunt

Abstract: TIPS seems to be a safe and effective treatment for symptomatic BCS and there is an obvious improvement in transplantation-free survival compared with conservatory medical treatment. It should, therefore, be considered early, as first-line intervention, in patients with insufficient response to medical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…BCS affects younger to mid-aged patients with the mean age of 40 y/o6. Clinical symptoms of BCS vary greatly depending on the course of disease.…”
Section: Discussionmentioning
confidence: 99%
“…BCS affects younger to mid-aged patients with the mean age of 40 y/o6. Clinical symptoms of BCS vary greatly depending on the course of disease.…”
Section: Discussionmentioning
confidence: 99%
“…HV occlusive BCS is difficult to diagnose and often mistaken for hepatic cirrhosis, liver carcinoma, or BCS with IVC occlusion. Recently, HV angioplasty, transjugular intrahepatic portosystemic shunt (TIPS), and modified TIPS have become the main treatments for HV occlusive BCS [3][4][5]. Rapid and effective recovery of HV and portal vein (PV) blood flow can promote the control of bleeding and ascites as well as the recovery of liver function.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some confirmation about the opportunity of early TIPS for BCS has been reported [49,50] . In fact, a group from China reported data on 100 patients with BCS with diffuse occlusion of HVs out of 377 BCS from January 2007 to December 2010.…”
Section: Early Versus Delayed Interventional Treatment Of Bcsmentioning
confidence: 96%
“…Both one-and five-year transplantfree survival was 100% and 93%, respectively. The authors concluded that TIPS is a safe and effective treatment for symptomatic BCS and should be considered the firstline intervention in patients with insufficient response to medical treatment [50] .…”
Section: Early Versus Delayed Interventional Treatment Of Bcsmentioning
confidence: 99%